Volume 99A, Number 7, July 2021 Cover Image. Issue 7 (1st July 2021) - Unknown
Abstract: Discriminating different cells types within kidney tissue simply by size, shape and structure of their cell nuclei is possible if it is supported by deep learning engines. This is what Woloshuk and colleagues succeeded to perform using 3D reconstructed nuclei from confocal images (read more in Woloshuk et al. this iss PP.https://doi.org/10.1002/cyto.a.24274 ). Read this amazing work and more from this months 'collection of research on cell classification by image cytometry supported by artificial intelligence.